(3fXGe GdejQGK Hjf GdbGfhf GdQheGfi hGdTQjYI GdESdGejI (B: s (3OQGSI JGQjNjI bGfhfjI ebGQfI (B/ s - (3eMeO CMeO eJhdjs; (3eMehO GdSbGs; (3LGeYI GdbGgQIs (3cdjI GdMbhbs ((3GdbGgQI (B: s (3cdjI GdMbhb(B- (3LGeYI GdbGgQI,s, 2008)
(3fSJNdU ef Jdc GdQSGdI hGdJi JMed YfhGf(B((3fXGe GdEQK ai GdbGfhf GdQheGfi hGdTQjYI GdESdGejI (B- (3OQGSI ebGQfI(B)(3ai CfgG JMJhi Ydi ebOeI MhJ YehejGJ Hjf GdbGfhf GdQheGfi hGdTQjYI GdESdGejI hGdYdGbI HjfgeG hHjGf GdQCjjf GddPjf bGdG ChdGgeG JCKjQ GdTQjYI GdESdGejI HGdbGfhf GdQheGfi heOi gPG GdJCKQ hKGfjgG HGSJbdGd GdTQjYI GdESdGejI hYOe JCKQgG HGdbGfhf GdQheGfj(B.s
(3CWQhMI(B((3OcJhQGg(B) - (3LGeYI GdbGgQI, cdjI GdMbhb, bSe adSaI GdbGfhf hJGQjNg (B2008.s
(3jTJed Ydi EQLGYGJ HHdjhLQGajI(B: (3UaMI (B682-701.s
(3GdedNU HGddZI GdYQHjIs
Keywords: (3GdbGfhf GdQheGfjs; (3GdTQjYI GdESdGejIs; (3GdEQKs; (3GdehGQjKs; (3GdhUjIs; (3QSGFd LGeYjIs -- (3LGeYI GdbGgQIs -- (3adSaI GdbGfhfs